Caste - Jodhka, Surinder S. (New Delhi : Oxford University Press, 2012)
The Oxford India Short Introductions are concise, stimulating, and accessible guides to different aspects of India. Combining authoritative analysis, new ideas, and diverse perspectives, they discuss subjects which are topical yet enduring, as also emerging areas of study and debate. The highly complex, dynamic, and enduring social reality of caste in India remains an anathema for social theorists. Combining up-to-date research with accessible and systematic exposition, this short introduction provides an exciting synoptic view of all the main aspects and dimensions of caste in India today. Looking at caste as tradition, as a constitutive element in power politics, and its inherent strands of humiliation and contestation in modern times, this book covers the many themes and issues around the lived reality of caste in India. It will prove indispensable for scholars, students, and general readers interested in this all-pervasive element of Indian social life.
It include index pages
Includes bibliographical references (p. [178]-192) and index.
Keywords: Caste -- India; India -- Social conditions